2016
DOI: 10.1007/s11325-016-1315-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between continuous positive airway pressure and circulating omentin levels in patients with obstructive sleep apnoea

Abstract: OSAS is associated with low serum omentin levels, and these levels can be reversed by effective CPAP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…It also demonstrated that a low omentin level could be regarded as a specific diagnostic marker for the occurrence and deterioration of OSAS [ 61 ]. Uygur et al [ 106 ] reported that the lower serum omentin level in OSAS can be reversed by CPAP treatment, which also confirmed the previous observations. More investigations are required to understand the exact roles and mechanisms of omentin in OSAS.…”
Section: Roles Of Omentin In Pulmonary Diseasesupporting
confidence: 77%
See 2 more Smart Citations
“…It also demonstrated that a low omentin level could be regarded as a specific diagnostic marker for the occurrence and deterioration of OSAS [ 61 ]. Uygur et al [ 106 ] reported that the lower serum omentin level in OSAS can be reversed by CPAP treatment, which also confirmed the previous observations. More investigations are required to understand the exact roles and mechanisms of omentin in OSAS.…”
Section: Roles Of Omentin In Pulmonary Diseasesupporting
confidence: 77%
“…Importantly, omentin increased endothelial NO expression, mitigated inflammation, and oxidation in human endothelial cells [ 70 , 71 ]. However, studies for determining omentin levels in OSAS patients have yielded contradictory results [ 61 , 62 , 63 , 106 ]. Two studies reported that omentin levels increased in patients with OSAS [ 62 , 63 ], whereas the levels of omentin in plasma were reduced to normal values after continuous positive airway pressure (CPAP) therapy for three months, [ 63 ]; unfortunately, the sample sizes used in these studies were small.…”
Section: Roles Of Omentin In Pulmonary Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand the reduced omentin levels are related with atherosclerosis, hypertension, cardiovascular disease and obstructive sleep apnea [26,28]. Omentin is inversely correlated with BMI, insulin resistance and positively with HDL and adiponectin [29].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al also found that plasma omentin-1 levels were significantly lower in 30 overweight male patients with severe OSA compared to 20 controls [86]. Besides, CPAP can restore omentin-1 levels in the serum, and effective 3-month CPAP treatment can reverse low omentin-1 levels in patients with OSA [87].…”
Section: Correlation Between Osa and Omentin-1mentioning
confidence: 94%